Transition metal-depleted graphenes for electrochemical applications via reduction of CO2 by lithium - Poh, Hwee Ling (2014)
Graphene has immense potential for future applications in the electrochemical field, such as in supercapacitors, fuel cells, batteries, or sensors. Graphene materials for such applications are typically fabricated through a top-down approach towards oxidation of graphite to graphite oxide, with consequent exfoliation/reduction to yield reduced graphenes. Such a method allows the manufacture of graphenes in gram/kilogram quantities. However, graphenes prepared by this method can contain residual metallic impurities from graphite which dominate the electrochemical properties of the graphene formed. This dominance hampers their electrochemical application. The fabrication of transition metal-depleted graphene is described, using ultrapure CO2 (with benefits of low cost and easy availability) and elemental lithium by means of reduction of CO2 to graphene. This preparation method produces graphene of high purity with electrochemical behavior that is not dominated by any residual transition metal impurities which would dramatically alter its electrochemical properties. Wide application of such methodology in industry and research laboratories is foreseen, especially where graphene is used for electrochemical devices.